Clutch size variation in passerine birds: The nest predation hypothesis - Slagsvold, Tore (Oecologia, 1982)
The hypothesis that a negative relationship exists between clutch size and the probability that the nest will be robbed is tested, using data for passerine birds given in the literature. The data for four separate groups of species, viz. hole-nesters, semi hole-nesters and open-nesters nesting above and on the ground, respectively, were examined in relation to geographical gradients and seasonal and annual variation. In general, the data analysis results support the hypothesis, but cannot yet be considered as proven. More data on the riks of nest predation are needed. The most serious discrepancy is that for the Fieldfare, the protection from predation provided by nesting in colonies does not seem to be accompanied by a corresponding increase in clutch size. However, the clutch size of the Brambling, a species with seeks out such colonies for its breeding sites, does tend to increase in these hatitats.The pattern of clutch size variation was similar for the two groups of hole-nesting species, but differed significantly from that found for the two groups of open-nesters. The difference in the clutch size variation of the two groups of open-nesting species predicted from the hypothesis, viz. that, in northern regions, both latitudinal and altitudinal increases in clutch size should more commonly be found for those species which nest on the ground, compared to those nesting above ground level, was confirmed.A seasonal decrease in clutch size, in temperate regions, was found to be typical for species whose nests are subject to relatively little predation, particularly for those species which have a short breeding season. Advantages of laying small clutches, resulting in fewer nestlings than the number which would be possible for the parents to rear successfully, are discussed, and a simple model is presented which does not assume that nest predation is dependent on clutch size.